Legal Position Of Substitute Money As A Preferent Right In Corruption Cases - Dewangga Putra Sunartedjo; Yuliati Yuliati; Reka Dewantara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Corruption is a form of crime that has a broad impact on the social, economic, and political development of a country. Law enforcement in corruption crimes is not only aimed at imposing sanctions on the perpetrators, but also to recover state losses through replacement money. The purpose of this study is to analyze the legal position of replacement money as a privilege in corruption cases. This type of research is normative juridical (legal research) with a statutory and conceptual approach. The author uses three types of legal materials, namely primary legal materials, secondary legal materials, and tertiary legal materials. The legal material search technique that the author applies is a literature study to find primary legal materials and secondary legal materials as well as expert opinions. The legal material analysis technique used in this study is systematic and grammatical interpretation. The results of the study show that the legal position of substitute money in corruption cases gives priority to recovering state losses over other debts. In Indonesian law, substitute money must be paid by corrupt individuals as part of their punishment, ensuring the state can reclaim lost assets before fulfilling other obligations, such as civil debts. This prioritization, outlined in the Corruption Crime Law (UU Tipikor), reflects the state's commitment to recovering financial losses and deterring future corruption by emphasizing both legal and financial consequences for perpetrators.